Potential Reduction of Stress Levels and Improving Vaname (Litopenaeus vannamei) Growth Performance with Probiotic Application - Darsiani Darsiani; Cici Nurul Annisa; Zulfiani Zulfiani; Dewi Yuniati; Teuku Fadlon Haser; Chairul Rusyd Mahfud; Shobrina Silmi Qori Tartila; Antoni Harahap; Suri Purnama Febri (Airlangga University, 2024)
The aim of this research was to find the most effective type of probiotic for the growth, survival, and stress resistance of L. vanamei. L. vanamei shrimp measuring PL 13 with a density of 2 fish/L of water were used as subjects for this research, which was conducted at the Poniang Beach Fish Seed Center from July 27 to September 24, 2023. This study was conducted using a completely randomized design (CRD) and consisted of four treatments and three repetitions, namely the operational standard, Bacillus sp., Lactobacillus sp., and a combination of Bacillus sp. and Lactobacillus sp. with a dose of 20 ml/kg mixed into feed containing 30% protein. The results of the study showed that the use of probiotics had no significant impact (p > 0.05) on the growth and survival of L. vanamei.